The Shade - Robinson, James, 1963- (DC Comics, 2013)
"After a brutal attempt on his life, the Shade leaves Opal City to learn which of the many people he has crossed are responsible. Joining forces with allies such as private detective Will von Hammer and teenaged vampire La Sangre, the Shade begins a centuries-spanning quest that takes him from Australia to Barcelona to London, facing off against lizard gods, celestial pharaohs, and even family members ... "--P. [4] of cover.